INDEKS KEPUASAN PASIEN SUATU RUMAH SAKIT SWASTA DI PURWOKERTO - Jebul Suroso (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
Sickhouse as health service medium make serious effort to reached a quality health service, achievable, and to raise medical patient satisfaction. This research head for identifying people satisfactory or people evaluation concerning a health service at take care of overnight installation, take care of pass, radiology, farmacy, and laboratory at a non-government sickhouse, include 14 service elements, in Purwokerto. This research design is descry foriptive by surveying technique invoked 120 respondents, comprise patients and expatients from the sickhouse that is takeabled with technique of random sampling proportional. Service Performance method would be used to analyse with the result that index of people satisfactory is good (B) for take care of overnight installation, take care of pass, radiology, farmacy, and laboratory. Disciplinary employee and punctuality being the top score aspects at five area services the sickhouse. There is index of people satisfactory C for polite behavior and sociability of registration employee. There is no component with A (very good) score. Result of this research was suggested to be judgement matter for the sickhouse management to raise quality service, especially in the patient registration. Keywords: satisfactory, patient, sickhouse